MODEL PENEMUAN HUKUM DENGAN METODE MAQASHID SYARIAH SEBAGAI JIWA FLEKSIBELITAS HUKUM ISLAM - Azmi Sirajuddin (Istinbath : Jurnal Hukum, 2016)
Finding the law in the Islamic law by Maqashid Syariah Method as a soul of Islamic law flexibility is very important and urgent in social life especially in a moslem society and it is one of way to be the best in stepping forward and progressing for a muslim country toward a moslem society and a moslem citizen in order to get a victory and a progress in facing many cases in this modern living and to get the best foundation in finding a new formula in an Islamic law and a new soul as the method in understanding and finding a new formula in solving many life problems especially in economic challengers for moslem society where and whenever they are. This is a big problem for a moslem intellectual to sharing their knowledge and science in getting new formulas in Islamic law for helping muslim’s problems and cases either social’s cases or nation’s cases to set up and build up something different with other cases of other religions. Islamic law is different from other laws as Josep Schract said: Islam is the religion of law and Christian is the religion of theology. At the present to solve the economic problems belong to muslim’s problem either in their life inside social climate or in board religious affair that those problems in economy can be solved by maqashid syariah as the excellent method in finding a new formula in Islamic law as Allah’s gracious toward His Ummah. The conflict theory is a method which is always true and exist in social life and social climate as Allah’s grant toward His Worshippers in this world. So this theory gives functions as the result of human’s life in facing many problems and cases. Human life must be exist and stand to continue their life in this world. In this case, the judges must be able to form a new law based on the maqashid syariah.